African music : a people's art - Bebey, Francis (Westport : Lawrence Hill, 1975)
Translation of Musique de l'Afrique. " Sewlective discography, revised and updated by Richard Hill": p. [149]- 173.
"Recent recordings": p. 174-176.
Includes bibliographical references
Keywords: Music -- Africa -- History and criticism